INFORMATION SYSTEM FOR MANAGEMENT PROSPERITY COUNCIL OF MOSQUE - Deni Heryanto (INTERNAL (Information System Journal), 2021)
This study discusses the proposed information system design for the Mosque Prosperity Council. This SI is expected to facilitate every management, such as recording asset information, cash management information, and religious activities. The purpose of this research is in addition to reducing the control of the mosque organization as well as to facilitate the delivery of information to the local community because this system is designed how the data can be accessed anywhere and anytime without time limits and to support this, one of them is by integrating it on a website. The method used in this research is to use the System Development Life Cycle (SDLC) to develop a software system, which consists of several stages, including planning, analysis, design, implementation, testing, and management, that form a workflow for planning and controlling. Information Systems. The result of this research is the application of the SI website, which helps facilitate the management of the Mosque Prosperity Council and increasing the ease with which the public can receive all this information.